The Use of Next-Generation Sequencing in Movement Disorders - Krebs, Catharine E.; Paisan-Ruiz, Coro (Frontiers in Genetics, 2012)
New advances in genomic technology are being introduced at greater speeds and are revolutionizing the field of genetics for both complex and Mendelian diseases. In movement disorders, this was first evidenced with the large number of genome-wide association studies (GWAS) by whole genome analyses performed in some neurological phenotypes, including Parkinson’s disease and progressive supranuclear palsy. But these high-throughput SNP genotyping assays not only allow us to perform GWAS in the idiopathic forms of a disease but also linkage analyses in families previously considered too small to power genetic analyses. Additionally, the role of copy number variation in human health and disease may perfectly be examined by the use of SNP-based arrays. Using this latter technology, others and we have repeatedly shown that pathogenic mutations in a single gene are responsible for different clinical entities and mutations in different genes can cause the same clinical entity. This is now being highlighted with the use of next-generation sequencing technologies, underlying the need to search for major genes and genetic modifiers that contribute to the phenotypic expression of movement disorders. By and large, the diagnosis of many movement disorders is becoming increasingly complex and as such both thorough clinical examinations and extensive molecular investigations are required to establish an accurate genotype-phenotype relationship. Furthermore, functional and cellular analyses should be performed to further prove pathogenecity. In this review, we summarize the latest genetic discoveries made by the use of next-generation sequencing technologies and purpose future directions and challenges to truly understand the pathophysiology of movement disorders.